Brokers and Finders in Startup Offerings - Yimfor, Emmanuel (Journal of Financial and Quantitative Analysis, 2025)
Abstract This study analyzes Form D filings to understand brokered startup offerings. About 60% of brokers are FINRA-registered; the rest, “finders,” are not. Startups with fewer seasoned investors and more local brokers tend to use brokers. Venture capital firms rarely join brokered offerings, but non-accredited investors do, especially offerings with finders. Overall, brokers aid in raising capital. Yet, startups using finders often fail to exit successfully and close following funding. This implies finders might be directing funds from non-accredited investors to lower-quality startups. Brokers help startups raise money without VC support, but the effectiveness of this capital allocation is unclear.